Dawning of a New Age? Economics Journals' Data Policies on the Test Bench - Sven Vlaeminck (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2021)
In the field of social sciences and particularly in economics, studies have frequently reported a lack of reproducibility of published research. Most often, this is due to the unavailability of data reproducing the findings of a study. However, over the past years, debates on open science practices and reproducible research have become stronger and louder among research funders, learned societies, and research organisations. Many of these have started to implement data policies to overcome these shortcomings. Against this background, the article asks if there have been changes in the way economics journals handle data and other materials that are crucial to reproduce the findings of empirical articles. For this purpose, all journals listed in the Clarivate Analytics Journal Citation Reports edition for economics have been evaluated for policies on the disclosure of research data. The article describes the characteristics of these data policies and explicates their requirements. Moreover, it compares the current findings with the situation some years ago. The results show significant changes in the way journals handle data in the publication process. Research libraries can use the findings of this study for their advisory activities to best support researchers in submitting and providing data as required by journals.
Keywords: 330; data policies; journals; open science; reproducibility